Does Agricultural Employment Benefit From Eu Support? - Sandy Dall'erba; Eveline Van Leeuwen (European Regional Science Association (ERSA), 2006)
Studies dealing with the impact of public support on employment have given varying results, depending on the estimation process, sample and type of subsidy. In this paper, we investigate the impact of support from the Common Agricultural Policy and Objective 5 funds on agricultural employment changes in European regions. We use a spatial econometric approach to consider the fact that employment dynamics in one region also depend on the dynamics of its neighbors. Our conclusions raise interesting issues for the ongoing debate on the role of support to the agricultural sector and provide several policy perspectives for the new member countries where this sector still influences economic performance.
Keywords: 330